Sorghum Feeding on the Nutritional Status of Body Fat Percentage in Patients with Type 2 Diabetes melitus - Zahra, Hanifah Umi; Dwipajati, Dwipajati; Palupi, Fitria Dhenok (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Dietary management is essential in treating diabetes melitus, with recommendations to limit carbohydrate intake and increase fiber consumption. Modifying both the amount and type of food supports blood glucose control. Sorghum, a local cereal with a low glycemic index of 41 and high fiber content, also contains antidiabetic phenolic compounds, including phenolic acids, flavonoids, and tannins. This study aimed to evaluate the impact of sorghum as an alternative staple food on body mass index (BMI) and body fat percentage in individuals with type 2 diabetes mellitus in Mulyorejo village, Malang City. The study also assessed the relationship between the order of fruit and vegetable consumption, sleep quality, blood glucose, and blood pressure in these patients. An experimental pre-post test control group design was used with 32 subjects. Statistical analysis employed the Wilcoxon difference test at a 95% confidence level (p-value < 0,05). Sorghum intervention significantly reduced BMI (p-value = 0,021 in both groups). For body fat percentage, the p-value was 0,377 in the control group and 0,026 in the treatment group. In summary, incorporating sorghum using the T model plate approach may help reduce BMI and body fat percentage.